Common land in English painting, 1700-1850 - Waites, Ian (Garden and landscape history, 2012)
During the eighteenth and nineteenth centuries, much of England's common land was eradicated by the processes of parliamentary enclosure. However, despite the fact that the landscape was frequently viewed as unproductive, outmoded and unsightly, many British landscape painters of the time - including Constable, Gainsborough and Turner - resolutely continued to depict it. This book is the first full study of how they did so, using evidence drawn not only from art-historical picture analysis, but from contemporary poems and novels, and the contemporary pamphlets, essays and reports that advanced the rhetoric of both agricultural improvement and new theories on landscape aesthetics. It highlights a deep-rooted social and cultural attachment to the common field landscape, and demonstrates that common land played a significant but - until now - underestimated role in both the history of English art and of the formation of an English national identity, reflecting what are still highly sensitive issues of progress, nostalgia and loss within the English countryside. Recasting common land as a recurrent facet of English culture in the modern period, the numerous paintings, drawings and prints featured in this book give the reader a comprehensive and evocative sense of what this now almost wholly lost landscape looked like in its hey-day. Ian Waites is Senior Lecturer in History of Art and Design at the University of Lincoln.